Art of transition: A Deleuzoguattarian framework. Issue 4 (December 2022) - Rose, Emma; Bingley, Amanda; Rioseco, Macarena
This article reflects on a funded participatory artmaking project that engaged displaced people whose traumatic experiences prior to exile in the UK necessitated referral for psychological support. Reflections are informed by action research method involving a cyclical reflexive feedback loop, augmented by intra-action and deterritorialisation. Within this context, the Deleuzoguattarian framework is used to add insights into artmaking as a deterritorialising vector of destabilization to identify beneficial shifts in participants' narratives of self in transition between the original homeland and the new environment. Artworks understood through the clients' voices over the course of ten weeks, suggest transition from a repetition of original trauma to artworks focused on present lives, and more positive agency. The article explores how witnessing and being witnessed, in the context of emerging intra-actions and transitions, integrate the authors within those processes, authors and clients becoming part of each other's new self-narratives.